Technology Puts Out the Firemen - Gosselin, Émile (Relations industrielles / Industrial Relations, 1958)
SummaryThe following text analyzes the dispute which culminated in a strike involving the Brotherhood of Locomotive Firemen and Enginemen and the Canadian Pacific Railway. It deals with the complex problems of technological change in a continent-wide economic setting, and suggests structural modifications of the unions concerned in order to adequately cope with them.